Migratory lineages rapidly evolve larger body sizes than non-migratory relatives in ray-finned fishes. Issue 1918 (15th January 2020) - Burns, Michael D.; Bloom, Devin D.
Abstract : Migratory animals respond to environmental heterogeneity by predictably moving long distances in their lifetime. Migration has evolved repeatedly in animals, and many adaptations are found across the tree of life that increase migration efficiency. Life-history theory predicts that migratory species should evolve a larger body size than non-migratory species, and some empirical studies have shown this pattern. A recent study analysed the evolution of body size between diadromous and non-diadromous shads, herrings, anchovies and allies, finding that species evolved larger body sizes when adapting to a diadromous lifestyle. It remains unknown whether different fish clades adapt to migration similarly. We used an adaptive landscape framework to explore body size evolution for over 4500 migratory and non-migratory species of ray-finned fishes. By fitting models of macroevolution, we show that migratory species are evolving towards a body size that is larger than non-migratory species. Furthermore, we find that migratory lineages evolve towards their optimal body size more rapidly than non-migratory lineages, indicating body size is a key adaption for migratory fishes. Our results show, for the first time, that the largest vertebrate radiation on the planet exhibited strong evolutionary determinism when adapting to a migratory lifestyle.